Screening of sesame (Sesamum indicum L.) genotypes for leaf potassium accumulation under drought stress environments: Screening of sesame (Sesamum indicum L.) genotypes for leaf potassium accumulation under drought stress environments - BRIJ B PANDEY,; P RATNAKUMAR,; K RAMESH,; G S LAKSHMI,; A GUHEY, (Journal of Oilseeds Research, 2020)
Sesame (Sesamum indicum L.) an orphaned, neglected, multipurpose oilseed crop, which is least explored for systematic research and tolerance to abiotic stresses, such as drought. Leaf K in maintaining the plant water status, stomatal regulation and plant survival when exposed to various abiotic stresses is well known. An experiment was carried out to screen 71 available genotypes for leaf K accumulation pattern. The results revealed that under water stress conditions irrespective of the genotype, leaf K content was found to increase and was highly correlated with seed yield and RWC content although there were variations among the genotypes. This suggested the possible role of K in conferring stress tolerance in sesame.